نحو تنمية بديلة ومستقلة في العالم العربي من منظور حضاري - البلي, مسعود (revue mofakir; No 12 (2015): مجلـــة المفكــر, 2018)
‫‪‫‪development‬‬ ‫‪take‬‬ ‫‪a‬‬ ‫‪big‬‬ ‫‪plenum‬‬ ‫‪in‬‬ ‫‪the‬‬ ‫‪political‬‬ ‫‪science,‬‬ ‫‪since‬‬ ‫‪the‬‬ ‫‪late‬‬ ‫‪fifties‬‬ ‫‪and‬‬ ‫‪early‬‬ ‫‪sixties‬‬ ‫‪,‬‬ ‫‪especially‬‬ ‫‪in‬‬ ‫‪the‬‬ ‫‪study‬‬ ‫‪of‬‬ ‫‪modernization‬‬ ‫‪in‬‬ ‫‪the‬‬ ‫‪third‬‬ ‫‪world‬‬ ‫;‪countries‬‬ ‫‪starting‬‬ ‫‪with‬‬ ‫‪the‬‬ ‫‪thesis‬‬ ‫‪of‬‬ ‫‪growth,‬‬ ‫...‪progress‬‬ ‫‪to‬‬ ‫‪the‬‬ ‫‪idea‬‬ ‫‪of‬‬ ‫‪sustainable‬‬ ‫‪development‬‬ ‫‪.But‬‬ ‫‪are‬‬ ‫‪these‬‬ ‫‪theses,‬‬ ‫‪valid‬‬ ‫‪for‬‬ ‫‪the‬‬ ‫‪Arab‬‬ ‫?‪region‬‬ ‫‪This‬‬ ‫‪article‬‬ ‫‪seeks‬‬ ‫‪to‬‬ ‫‪shed‬‬ ‫‪light‬‬ ‫‪on‬‬ ‫‪the‬‬ ‫‪development‬‬ ‫‪models‬‬ ‫‪in‬‬ ‫‪Western‬‬ ‫‪thought,‬‬ ‫‪and‬‬ ‫‪the‬‬ ‫‪extent‬‬ ‫‪of‬‬ ‫‪its‬‬ ‫‪impacts‬‬ ‫‪on‬‬ ‫‪the‬‬ ‫‪Arab‬‬ ‫‪region,‬‬ ‫‪and‬‬ ‫‪try‬‬ ‫‪to‬‬ ‫‪imagine‬‬ ‫‪an‬‬ ‫‪alternative‬‬ ‫‪development‬‬ ‫‪model,‬‬ ‫‪in‬‬ ‫‪the‬‬ ‫‪context‬‬ ‫‪of‬‬ ‫‪Arab‬‬ ‫‪civilization.‬‬